Cabo Verde Economic Update : Cabo Verde’s Potential Digital Dividends - World Bank (Washington, DC : World Bank, 2022)
The second Economic Update for Cabo Verde focuses on the importance of returning to fiscal sustainability in the aftermath of the COVID-19 crisis and on the potential role of Information and Communications Technology (ICT) in strengthening the foundations for a sustainable and inclusive economic recovery. The first chapter discusses the current macroeconomic situation, outlook, and risks the country faces over the medium term. The second chapter provides an overview of key challenges to transform Cabo Verde into a Digital Hub. The report offers a set of actionable policy priorities for a swift return to fiscal and debt sustainability and around the national digital transformation agenda, which include enhancing the ownership of the innovation agenda, strengthening digital foundations, investing in human capital, and mobilizing Diaspora resources to create a private ICT sector.